2011
DOI: 10.1103/physreva.84.043844
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of dark state of an open atomic system in constant intensity laser field

Abstract: We studied experimentally and theoretically the evolution of open atomic systems in the constant intensity laser field. The study is performed by analyzing the line shapes of Hanle electromagnetically induced transparency (EIT) obtained in different segments of a laser beam cross section of constant intensity, i.e., a -shaped laser beam. Such Hanle EIT resonances were measured using a small movable aperture placed just in front of the photodetector, i.e., after the entire laser beam had passed through the vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In the wings of the Gaussian laser beam, a Ramsey-like effect can reshape EIT resonances with respect to those near the laser beam centre, as shown in [16,17]. For the profile, optical pumping to the uncoupled ground level dominantly influences the line-shape [18]. The theory demonstrates that the atomic dark state is more sensitive to magnetic field when the atoms are traversing the Gaussian laser beam than when passing through a constant intensity field of the laser beam.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In the wings of the Gaussian laser beam, a Ramsey-like effect can reshape EIT resonances with respect to those near the laser beam centre, as shown in [16,17]. For the profile, optical pumping to the uncoupled ground level dominantly influences the line-shape [18]. The theory demonstrates that the atomic dark state is more sensitive to magnetic field when the atoms are traversing the Gaussian laser beam than when passing through a constant intensity field of the laser beam.…”
Section: Resultsmentioning
confidence: 94%
“…The importance of the laser beam profile on the EIT was indeed demonstrated theoretically for the vacuum [26] and the buffer gas cells [23][24][25]. Our previous studies have shown that the evolution of the states of the atoms passing through laser beams of different profiles is governed by distinct physical processes [17,18]. Consequently, line-shapes of EIT resonances obtained from various segments of the laser beam cross-section reflect these differences.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Therefore, it is important to take into account the real laser beam profile for proper modeling and analysis of coherent effects in alkali-metal vapors. Subsequent sections will present the details of the work published in [53,54,55].…”
Section: Influence Of Laser Intensity and Beam Profile On Hanle Resonmentioning
confidence: 99%